Lipoblastoma of scalp in a 4-month-old patient: an extremely rare case report and review of the literature - Demir, Fatih; Ozturk, Sait; Balta, Hilal; Erol, Fatih Serhat (Springer, 2022)
Lipoblastoma is a rare benign tumor originating from adipose tissue, usually seen in infancy and early childhood. Here, we present a case of scalp lipoblastoma in a 4-month-old that we treated surgically and review the literature. Although lipoblastomas may be seen in various locations during infancy and early childhood, rarely, they can also develop in the scalp.
Keywords: Lipoblastoma; Scalp; Pediatric